2019
DOI: 10.1038/s41598-018-36445-6
|View full text |Cite
|
Sign up to set email alerts
|

High lactose whey cheese consumption and risk of colorectal cancer - The Norwegian Women and Cancer Study

Abstract: The incidence of colorectal cancer (CRC) has increased among Norwegian women, and is among the highest in the world. In order to understand this increase, country specific dietary exposures have been investigated. The aim of this study was to quantify the association between consumption of brown cheese, a common bread topping in Norway, and colorectal, colon, and rectal cancer in the prospective Norwegian Women and Cancer (NOWAC) Study. Data on brown cheese consumption and adjustment factors was available for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…12,13 High intake of milk products have shown to be protective, but the association is weak and it is not clear which nutrients, i.e lactose, vitamin D or dietary calcium, that would be responsible for the risk reduction. 12,[14][15][16] Other protective factors might be high intake of dietary fibres, although the ideal source of fibre is not determined. 17 High physical activity has been shown to reduce the risk for colon cancer, but the effect on RC is not as convincing.…”
Section: Risk Factorsmentioning
confidence: 99%
“…12,13 High intake of milk products have shown to be protective, but the association is weak and it is not clear which nutrients, i.e lactose, vitamin D or dietary calcium, that would be responsible for the risk reduction. 12,[14][15][16] Other protective factors might be high intake of dietary fibres, although the ideal source of fibre is not determined. 17 High physical activity has been shown to reduce the risk for colon cancer, but the effect on RC is not as convincing.…”
Section: Risk Factorsmentioning
confidence: 99%
“…The association between egg intake and CRC risk is inconsistent, with some studies reporting a positive association ( Aune et al., 2009 ; Lee et al., 2009 ) while others reported a null association ( Franceschi et al., 1997 ; Järvinen et al., 2001 ). On the other hand, dairy products are associated with a decreased colon cancer risk ( Huncharek et al., 2008 ; Aune et al., 2012 ), particularly cheese and milk ( Lee et al., 2009 ; Aune et al., 2012 ; Murphy et al., 2013 ; Barnung et al., 2019 ).…”
Section: The Interactions Between Diet Gut Microbiota and Colorectamentioning
confidence: 99%
“…In China, the incidence of colorectal cancer has been increasing, which is common in western nations 2 , 3 . Numerous studies have shown that CRC morbidity and mortality are closely related to the following factors: genetic variants 4 , race 5 , family 6 , age 7 , 8 , high fat intake 9 , 10 , red meat consumption, obesity 11 , alcohol consumption, smoking 12 , 13 and physical inactivity 14 , 15 . Currently, surgery and chemotherapy are the main methods used for treatment of colorectal cancer 16 .…”
Section: Introductionmentioning
confidence: 99%